The brand gym a practical workout to gain and retain brand leadership - Taylor, David, 1964- (Wiley, 2010)
"This refreshingly simple, practical guide demonstrates how brand management can boost business performance. It is the ideal inspiration for creating growth in today's tough economic times. Following the template of the original version, the book consists of a programme of eight "Workouts" that will help marketers raise their own game in key areas such as insight, portfolio strategy, positioning and innovation"--